2006
DOI: 10.1111/j.1365-2753.2006.00645.x
|View full text |Cite
|
Sign up to set email alerts
|

The Finnish national asthma programme: communication in asthma care – quality assessment of asthma referral letters

Abstract: The Finnish National Asthma Programme calls for optimizing communication between doctors. The proportion of poor letters was 50% higher than the preset standard and clearly indicates a need for improvement. We found several issues, which need to be better communicated (smoking, lung function tests, wheezing, medication) when referring a patient with suspected asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 10 publications
2
12
0
1
Order By: Relevance
“…Figure 2 shows the origin of these spirometry reports. In our previous study, 14 all non-emergency referral letters (n=3176) to three Finnish pulmonary outpatient units sent during 2001 were scrutinised. The referrals originated from health care centres and private practices.…”
Section: O P Y R I G H T G E N E R a L P R A C T I C E A I R W A Y mentioning
confidence: 99%
“…Figure 2 shows the origin of these spirometry reports. In our previous study, 14 all non-emergency referral letters (n=3176) to three Finnish pulmonary outpatient units sent during 2001 were scrutinised. The referrals originated from health care centres and private practices.…”
Section: O P Y R I G H T G E N E R a L P R A C T I C E A I R W A Y mentioning
confidence: 99%
“…The only previous studies of respiratory referral letters relate to patients with asthma, and show similar omissions to those in other specialty areas with, for example, only 50% of referral letters recording the results of necessary investigations, 20 and 41% recording current medications. 21 Our study has obvious limitations in that the number of patient referral letters evaluated was small and the setting was limited to one NHS respiratory outpatients department. However, we have shown clearly that the tests ordered on the basis of a referral letter were substantially fewer than those ordered at the end of the consultation.…”
Section: Discussionmentioning
confidence: 99%
“…However, when asthma referral letters were evaluated against objective criteria 31 at several disease centres in Finland following the establishment of a National Asthma Programme, 44-45% were still considered to be of poor quality, and the inclusion of necessary information remained inconsistent despite specific referral recommendations. 20,21 Many specialties have produced and promoted standardised referral letters, guidelines and referral criteria, plus or minus specific education for GPs, 2,14,26,27,32 as a means to improve referral information. There has been some success with the use of structured forms; 15,16 however, the results are equivocal 19 and passive dissemination of guidelines has not been found to be an effective strategy to improve referral information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Single disease programs have shown that asthma and COPD patients receive better health care, impairment decreases, and fewer hospitalizations occur, provided that access to drugs is secured. ( 32 - 34 ) In addition, this type of programs reduces deaths and health expenditures in asthma and COPD, ( 35 ) which would be included in integrated programs.…”
mentioning
confidence: 99%